A 2.4 GHz 0.18-μm CMOS class E single-ended power amplifier without spiral inductors - Sohiful Anuar, Zainol Murad; Pokharel, R. K.; Kanaya, H.; Yoshida, K. (IEEE, 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/